Institutional Corruption and the Rule of Law - Gowder, Paul (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
The literature contains two concepts of corruption which are often confused with one another: corruption as twisted character (pollution), and corruption as disloyalty. It also contains two sites for corruption: the corruption of individuals, and the corruption of entire institutions such as a state or a legislature.This paper first draws a clear distinction between the pollution and disloyalty concepts of corruption in the individual context, and then defends a conception of disloyalty corruption according to which the distinguishing feature is an agent who uses powers delegated to her from her principal as her own. Then, the paper shifts gears to the institutional context, arguing that the best account of institutional corruption in the extant literature is of the pollution kind. It then fills the remaining logical space by laying out a conception of institutional corruption as disloyalty and explaining its moral significance for the political legitimacy of a democracy.